A process for conducting mixed methods data analysis - John W. Creswell; Machiko Inoue (Journal of General and Family Medicine)
Abstract The process of mixed methods data analysis has long been understudied and needs clear guidance for researchers. This review article honors Michael D. Fetters' pioneering work on mixed methods data analysis, building on his concepts of integration, joint displays, and metainferences. This review summarizes existing mixed methods data analysis discussions and proposes advanced steps for the analysis process. Our approach involves identifying a research problem, collecting diverse data, selecting a mixed methods design, integrating the data within the design, using joint displays for analysis, and drawing metainferences. We illustrate our methods with a Japanese empirical research study from family medicine. This article contributes to the field of mixed methods research by detailing a practical process approach to mixed methods analysis combining recent procedures in the field of mixed methods research.